Place, Space, Time: Media gatekeeping and iconic imagery in the digital and social media age. Issue 5 (3rd July 2016) - Dahmen, Nicole Smith; Morrison, Daniel D.
Abstract : Media gatekeeping has been a critical theoretical tenet in the formation of iconic images. Traditionally, news photographs became iconic, in large part, through their prominent placement on elite newspaper front pages. But as we move away rapidly from print news towards a digital news environment, what is the effect on this traditional tenet of iconicity? Additionally, with the rise of social media, elite media outlets are no longer the sole gatekeepers. Within the age of digital news and social media, this research seeks to understand differences between identification of iconic imagery, comparing a prompt of commonly used elite media images to an unprompted response in an effort to ascertain which images are, in fact, considered most iconic by audiences. The research also considers events across time, from historic events to more recent events that have fallen within the timeframe of the rise of digital news and social media. Findings indicate that the democratization of the news via social media has had the unanticipated effect of rescinding the uniformity of collective visual consciousness and the traditional formation of iconic imagery. Indeed, elite media outlets are no longer the sole dictators of "crowning images."